Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18147323
|View full text |Cite
|
Sign up to set email alerts
|

Parental Compliance towards Oral Health Education among Preschoolers with Special Healthcare Needs

Abstract: Background: Young children with special needs greatly rely on their parents to support their daily living activities; parental compliance may have great impact on the implementation of health promotion activities among those children. This study aimed to investigate the parental compliance towards oral health education (OHE) among children with special healthcare needs (SHCN). Method: The participants were 306 parents whose children had participated in a 24-month OHE program for preschool children with SHCN. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Interestingly, few researchers have analyzed the strength of the association between maternal SOC and the oral health behavior of SCHN children. Assessing this association becomes important as these children are dependent on maternal care [10]. Hence, the aim was to observe if there is an association between maternal SOC and the oral health behavior of children with SCHN.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, few researchers have analyzed the strength of the association between maternal SOC and the oral health behavior of SCHN children. Assessing this association becomes important as these children are dependent on maternal care [10]. Hence, the aim was to observe if there is an association between maternal SOC and the oral health behavior of children with SCHN.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 62.5% of parents or caregivers admitted that their children had difficulty brushing their teeth. Therefore, parents play an important role in guiding, reminding, and providing facilities so that children can maintain their oral health and hygiene ( 9 , 12 ). Parents or caregivers have a direct influence on their children's oral health maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Most research focusing on parents’ health literacy confirms the relationship between the HL level of parents and their children’s health outcomes [ 19 , 20 , 21 ]. In addition, to measure general HL among parents, several studies examined oral- [ 22 , 23 ], fever- [ 24 , 25 ], and pharmacotherapy literacy [ 26 , 27 ]. Disadvantaged parents with lower social status are emphasized in the design of studies on parental health literacy [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%